Collapse and Recovery of Green Fluorescent Protein Chromophore Emission through Topological Effects - Tolbert, Laren M; Baldridge, Anthony; Kowalik, Janusz; Solntsev, Kyril M (Accounts of chemical research, 2012)
Housed within the 11-stranded β-barrel of the green fluorescent protein (GFP) is the arylideneimidazolidinone (AMI) chromophore, the component responsible for fluorescence. This class of small-molecule chromophore has drawn significant attention for its remarkable photophysical and photochemical properties, both within the intact protein and after its denaturation. All of the proteins so far isolated that have visible light fluorescence have been found to contain an AMI chromophore. These proteins comprise an extensive rainbow, ranging from GFP, which contains the simplest chromophore, p-hydroxybenzylideneimidazolidinone (p-HOBDI), to proteins having molecules with longer conjugation lengths and a variety of intraprotein interactions. The fluorescence invariably almost vanishes upon removal of the protective β-barrel. The role of the barrel in hindering internal conversion has been the subject of numerous studies, especially in our laboratories and those of our collaborators. A better understanding of these chromophores has been facilitated by the development of numerous synthetic protocols. These syntheses, which commonly use the Erlenmeyer azlactone method, have evolved in recent years with the development of a [2 + 3] cycloaddition exploited in our laboratory. The synthetic AMI chromophores have allowed delineation of the complex photophysics of GFP and its derivatives. Upon denaturation, AMI chromophores are marked by 4 orders of magnitude of diminution in emission quantum yield (EQY). This result is attributed to internal conversion resulting from conformational freedom in the released chromophore, which is not allowed within the restrictive β-barrel. To date, the photophysical properties of the AMI chromophore remain elusive and have been attributed to a variety of mechanisms, including cis–trans isomerization, triplet formation, hula twisting, and proton transfer. Advanced studies involving gas-phase behavior, solvent effects, and protonation states have significantly increased our understanding of the chromophore photophysics, but a comprehensive picture is only slowly emerging. Most importantly, mechanisms in structurally defined chromophores may provide clues as to the origin of the “blinking” behavior of the fluorescent proteins themselves. One approach to examining the effect of conformational freedom on rapid internal conversion of the chromophores is to restrict the molecules, both through structural modifications and through adjustments of the supramolecular systems. We thus include here a discussion of studies involving the crystalline state, inclusion within natural protein-binding pockets, complexation with metal ions, and sequestration within synthetic cavities; all of this research affirms the role of restricting conformational freedom in partially restoring the EQY. Additionally, new photochemistry is observed within these restricted systems. Many of the studies carried out in our laboratories show promise for these molecules to be adapted as molecular probes, wherein inclusion turns on the fluorescence and provides a signaling mechanism. In this Account, we present an overview of the AMI chromophores, including synthesis, overall photophysics, and supramolecular behavior. A significant amount of work remains for researchers to fully understand the properties of these chromophores, but important progress achieved thus far in photophysics and photochemistry is underscored here.